(untitled) - Johnston, Michael V.; Michael V. Johnston; Robert A. Gross (Oxford,New York, 2008)
Principles of Drug Therapy, Second Edition provides comprehensive coverage of current drug therapy in neurology while providing the background information that neurologists and other clinicians need to understand its rationale. The range of new drugs available for treatment of neurological disorders is expanding rapidly along with rapid advances in the neurosciences that are uncovering disease mechanisms. Although there are many sources of drug information, most are limited to basic information about indications, dose and side effects. However the complexity of the nervous system is enormous and the information needed to understand drug effects is accordingly often not readily available in a single source. The book addresses that issue by presenting 18 focused, disease-related chapters by authors who are expert clinical sub-specialists as well as experts on drug therapy
Keywords: Neuropharmacology; Nervous system; Brain Diseases; Mental Disorders; Nervous System Diseases; Neurologic Manifestations